Advancing The Performance of Educational Administration Staff: A Study of Leadership Strategies In Madrasah Ibtidaiyah - Alauddin Alauddin; St. Marwiyah; Tandi Bunga (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The strategy of the head of the Madrasah in developing the performance of education personnel in Madrasah Ibtidaiyah DDI Kabera is the focus of this qualitative research. Data was collected from madrasah heads, education staff, and other involved parties and from school records, documents, and direct observations in the school environment. Data validity checks are performed through data triangulation to ensure consistency of findings. The data analysis technique used is thematic analysis. The results showed that the performance of education personnel in Madrasah Ibtidayah DDI Kabera can be categorized as good. They can complete tasks well and continue to improve their performance over time. Principals continuously evaluate performance using assessment tools, which contribute to their performance development. The principal's strategy for improving the performance of education personnel involves appreciation in the form of motivation, coaching, and encouragement. This boosts their passion for the task and improves its performance. A non-authoritarian leadership approach also plays a role in good cooperation between the principal and his staff. With the right strategy, the head of the Madrasah can create a meaningful and creative learning environment, improve the quality of education, and achieve the expected goals in Madrasah Ibtidayah DDI Kabera.